Revitalisasi Literasi Anak Melalui Pendekatan Membaca Aktif di Taman Baca PMI Medan Denai - Septa Septa; Fithria Rizka S; Dirmansyah Dirmansyah; Himma Dewiyana; Muhammad Rasyid Ridlo (Nawadeepa: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to revitalize children’s literacy enthusiasm through participatory and humanistic approaches at the PMI Reading Garden (Taman Baca PMI) in Medan Denai, Medan City, Indonesia. The program addressed the declining reading interest among children and the limited digital promotion skills of the library manager. The implementation involved 39 children aged 7–12 years and one library manager as the community partner. The methods used included active reading, retelling, and educational film discussions for children, along with one-on-one digital coaching for the library manager. Quantitative observations showed that 82% of participants were able to retell stories independently with good comprehension, and 95% actively participated during the activities. In addition, the library manager successfully reactivated the library’s social media account for promotional purposes. These results demonstrate that participatory-educational approaches effectively foster reading motivation and communication skills in children while empowering local literacy managers. This activity provides a replicable model of community-based literacy revitalization that is simple, low-cost, yet socially and educationally impactful.